Associations between RORγt and T-bet Expressions, clinicopathological indices and survival rate in oral Squamous cell carcinoma patients. (March 2023) - Ghelichli, Maryam; Mohtasham, Nooshin; Mohajertehran, Farnaz; Farshbaf, Alieh; Anvari, Kazem; Taghipour, Ali; Pakfetrat, Atessa; Ansari, Amir houshang
Highlights: RORγt and T -bet genes in tumor tissue compared to the surgical healthy margin have high overexpression in Oral SCC patients. RORγt and T -bet genes were more expressed in patients with higher grade and stage and in the surgical healthy margin less incidence than the tumor tissue. Overexpression of both genes can play critical role in the pathogenesis of OSCC. The surgical healthy margin of the tumors can be considered as a biological area for more detection of valuable biomarkers. Abstract: Background: Oral cancers are the sixth most common cancers around the world. According to the pivotal role of immune cells in the pathogenesis of oral squamous cell carcinoma (OSCC), as the frequent form of malignant epithelial neoplasm in the oral cavity, we investigated the association between the expression of RORγt and T -bet genes as two transcription factors, clinicopathologic indices, and survival rate. Methods and Materials: Forty-two OSCC paraffin embded-blocks tissue samples and their surgical healthy margins (as a control group) were collected. Demographic information like age and gender, and medical history including tumor stage/grade, and following-up time were registered. The RORγt and T -bet expression were assessed by qPCR. The overall survival (OS) and disease free survival (DFS) were analyzed by SPSS V.23 software. Results: The expression of RORγt and T -bet genes in OSCC patients were significantly higher than in surgical healthy margins (P < 0.001). Both expression demonstrated a significant difference between surgical healthy margins and tumor tissues related to gender and clinicopathological indices including stage and grade (P < 0.05). The expression of both genes in stage I patients was significant compared to stage IV (P < 0.05). The relation between expressions, OS, and DFS with clinical stage and histological grade of tumors was not statistically significant (P > 0.05). Conclusion: Overexpression of RORγt and T -bet in OSCC patients with higher grade and stage in compare to surgical healthy margin highlighted their critical role in OSCC pathogenesis including oral epithelial cell differentiation, tumorigenesis process, and malignant transformation. Moreover, both mentioned genes can apply as prognostic biomarkers in OSCC patients. We suggest surgical healthy margin be considered as valuable biological area.